Policy Implications on Carbon Labeling Scheme Toward Carbon Neutrality in China - Zhao, Rui; Wu, Dingye; Zhang, Junke (Frontiers in Environmental Science, 2021)
Carbon labeling scheme as a quantitative measure on carbon emissions of product or service, can be applied to leading low carbon consumption and production, which is also a powerful tool to achieve carbon neutral. The policy brief reviews the progress of carbon labelling scheme to provide insight into its future perspectives on carbon neutrality in China. The results show that: ① China has not officially fostered as a carbon labeling system, but there is a pilot attempt to electric appliance; ② Publics’ perception towards carbon labeling scheme is in a lower level; ③ There is a room for improvement on the existing carbon labeling scheme, to improve its transparency and comparison.